Myanmar Economic Monitor, October 2017 : Capitalizing on Investment Opportunities - World Bank Group (World Bank, Washington, DC, 2018)
Myanmar’s macroeconomic environment remains stable, though economic growth is estimated to have slowed to 5.9 percent in 2016-17 compared to 7 percent in 2015-16, weighed down by slower investment demand. Growth is projected to recover to 6.4 percent in 2017-18, though risks are tilted to the downside due to the recent escalation of tensions in Rakhine State and the potential stalling of the overall reform agenda. Baseline projections assume that the authorities will move to a medium-term economic reform program to sustain hard earned macroeconomic stability gains and accelerate inclusive growth. Accelerating much needed investments in the economy will also require progress on structural reforms in, among other areas, finance, energy, and business regulations. On access to finance, implementation of the recently adopted prudential regulations under the Financial Institutions Law are expected to support financial sector stability and to manage risks. The banking community however has sought more time to comply with the new regulations because current deadlines might put pressure on the financial system. Progress on reform of State Owned Banks is expected over the coming months starting with international audits. At the same time, steps to develop a secured transaction framework and credit bureau licensing should help to improve access to finance and credit quality. On access to electricity, priorities include finalizing the power sector master plan and associated decisions on dealing with gas supply shortages, electricity tariff adjustments with protection for vulnerable groups, and institutional reforms (e.g. establishment of regulatory agency). On business regulations, priorities include implementation of the 2016 investment law, adoption of the companies act, and aligning customs procedures in valuation of goods with international practices.